Perspectives of Students’ Behavior Towards Mobile Learning (M-learning) in Egypt: an Extension of the UTAUT Model - Ali, Reham Adel; Mohd Arshad, Muhammad Rafie (Engineering, Technology and Applied Science Research (ETASR), 2016)
The rapid development of third-generation (3G) mobile technologies has led to the emergence of a new kind of learning called mobile learning (m-learning). M-learning means the use of mobile devices to access learning materials at anytime and anywhere with the aid of mobile terminals and networks. This paper explores the possibility of applying m-learning for schools in Egypt through a proposed model of acceptance factors that may affect the students’ intentions to adopt m-learning. We use the original model of Unified Theory of Acceptance and Use of Technology (UTAUT) and extended it with three new factors mobility, interactivity, and enjoyment.